Assessment of Readiness for Mobility Transition (ARMT): A Tool for Mobility Transition Counseling With Older Adults. (June 2013) - Meuser, Thomas M.; Berg-Weger, Marla; Chibnall, John T.; Harmon, Annie C.; Stowe, James D.
Individualized assessment is important when counseling older adults concerning the transition from driving to nondriving mobility. This study validated a measure of emotional and attitudinal readiness in support of mobility transition counseling (MTC). Items derived from a mixed-methods approach were administered by mailed questionnaire to community-dwelling adults ( n = 297; ages 57-95). Factor analysis was employed to form the 24-item Assessment of Readiness for Mobility Transition (ARMT). The ARMT–Total Score (ARMT-TS) demonstrated sound internal consistency and split-half reliability (.88 each). The ARMT-TS correlated as hypothesized with validity measures, including self-reported physical functioning, mental health, and openness to experience. High scorers, who evidenced strong self-reliance and an unwillingness to be a burden on others, are considered to be at risk when faced with a significant mobility transition. An appreciation for such differences can allow for personalized, tailored discussion and planning for when it is time to "hang up the keys."